Therapeutic Potential of Pentoxifylline in Paraquat-Induced Pulmonary Toxicity: Role of the Phosphodiesterase Enzymes - Ghasemi, Farshad; Mohammadi, Mobina; Ghaffari, Fatemeh; Hosseini-Sharifabad, Ali; Omidifar, Navid; Nili-Ahmadabadi, Amir (Drug Research, 2024)
Pentoxifylline (PTX), a non-selective phosphodiesterase inhibitor, has demonstrated protective effects against lung injury in animal models. Given the significance of pulmonary toxicity resulting from paraquat (PQ) exposure, the present investigation was designed to explore the impact of PTX on PQ-induced pulmonary oxidative impairment in male mice.Following preliminary studies, thirty-six mice were divided into six groups. Group 1 received normal saline, group 2 received a single dose of PQ (20 mg/kg; i.p.), and group 3 received PTX (100 mg/kg/day; i.p.). Additionally, treatment groups 4–6 were received various doses of PTX (25, 50, and 100 mg/kg/day; respectively) one hour after a single dose of PQ. After 72 hours, the animals were sacrificed, and lung tissue was collected.PQ administration caused a significant decrease in hematocrit and an increase in blood potassium levels. Moreover, a notable increase was found in the lipid peroxidation (LPO), nitric oxide (NO), and myeloperoxidase (MPO) levels, along with a notable decrease in total thiol (TTM) and total antioxidant capacity (TAC) contents, catalase (CAT) and superoxide dismutase (SOD) enzymes activity in lung tissue. PTX demonstrated the ability to improve hematocrit levels; enhance SOD activity and TTM content; and decrease MPO activity, LPO and NO levels in PQ-induced pulmonary toxicity. Furthermore, these findings were well-correlated with the observed lung histopathological changes.In conclusion, our results suggest that the high dose of PTX may ameliorate lung injury by improving the oxidant/antioxidant balance in animals exposed to PQ.
Keywords: pentoxifylline; paraquat; lung toxicity; oxidative stress